THE EFFECTIVENESS OF USING TELL ME MORE (TMM) IN TEACHING ENGLISH SPEAKING AT SECOND YEAR STUDENTS OF SMA NEGERI 5 BARRU: An Experimental Research - Wardani, Irna; Ampa, Andi Tenri; Abdul, Nurdevi Bte (Journal of Computer Interaction in Education, 2018)
The research was aimed to improving the students’ Pronunciation ability, particularly vowel and consonant sounds in speaking by using Tell Me More (TMM) at Second Year Students of SMA Negeri 5 Barru. The method of this research was quasi experimental. It was consisted with two classes, namely experimental class and control class by used purposive sampling. The number of sample selected was 60 students. The data were obtained through pronunciation test. The result of this research, the researcher found: 1. the significant difference between the students who are taught consonant by using Tell Me More (TMM) and the students who are taught by using discussion method in teaching and learning pronunciation. Where 5.15 in pre-test to be 6.56 in post-test and control class was 4.83 in pre-test to be 5.53 in post-test. 2. The significant difference between the students who are taught vowel by using Tell Me More (TMM) and the students who are taught by using discussion method in teaching and learning pronunciation. Where 7.43 in pre-test to be 8.15 in post-test and in control class was 6.89 in pre-test to be 7.51 in post-test.